2003
DOI: 10.1108/09564230310465994
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumer motivation and behavior related to self‐scanning in retailing

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
81
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(93 citation statements)
references
References 23 publications
8
81
0
4
Order By: Relevance
“…Perceived usefulness is an important impact factor on self-service technology adoption according to many researches (Wang etc., 2003;Curran & Meuter, 2005; Amin,2007) [23][24][25]. The research of Dabholkar made in 2003 found that perceived ease of use is a determining factor to affect consumers using self-service [26].…”
Section: Self-servicementioning
confidence: 99%
“…Perceived usefulness is an important impact factor on self-service technology adoption according to many researches (Wang etc., 2003;Curran & Meuter, 2005; Amin,2007) [23][24][25]. The research of Dabholkar made in 2003 found that perceived ease of use is a determining factor to affect consumers using self-service [26].…”
Section: Self-servicementioning
confidence: 99%
“…Using SSTs can also provide some consumers with intrinsic benefits, such as feelings of independence and enjoyment (Dabholkar et al, 2003;Meuter et al, 2003). Some consumers even admitted using SSTs in order to avoid the personal contact with service employees (Dabholkar et al, 2003). Some of those identified reasons represent motives such as convenience, independence and cost savings, while habit and lack of other service delivery options may be regarded as conditions rather than motivations.…”
Section: Ssts In Multi-channel Service Environmentsmentioning
confidence: 99%
“…SSTs also require higher levels of consumer participation and responsibility, so they are perceived as riskier than personal services (Lee and Allaway, 2002). Even people who have favourable attitudes towards technology may avoid SSTs because they cannot replace the personal interaction (Dabholkar et al, 2003;Lee and Allaway, 2002), or they require a radical change in their consumer behaviour (Curran and Meuter, 2007).…”
Section: Ssts In Multi-channel Service Environmentsmentioning
confidence: 99%
See 2 more Smart Citations